Characterization of glutamine synthetase involved in the fecundity of Rhopalosiphum padi - Xing-Ye Li; Jie-Qiong Wang; Kang-Wu Zheng; Yu-Ting Li (Scientific Reports)
Abstract Glutamine synthetase (GS) is a pivotal enzyme crucial for the synthesis of glutamine (Gln), an important precursor in amino acid biosynthesis, essential for the growth, development, and reproduction of insects through its involvement in nitrogen metabolism. Despite its recognized significance in insect biology, the specific functions of GS in aphids have not been fully elucidated. Here, we cloned and characterized two GS genes, RpGS1 and RpGS2, from Rhopalosiphum padi and analyzed their expression profiles and explored the contribution of RpGS to aphid fecundity. The two isoforms, which are predicted to localize in the mitochondria and cytoplasm respectively, were successfully cloned and heterologously expressed in Escherichia coli. Despite exhibiting 92% amino acid similarity, the isoforms displayed distinct enzymatic kinetic properties and demonstrated variations in mRNA expression levels across developmental stages and tissues. Notably, RpGS1 was highly expressed in the head, whereas RpGS2 was highly expressed in the intestine. Both RpGS genes were significantly expressed in alate adult aphids. Treatment with the specific inhibitor L-methionine S-sulfoximine (MSX) not only suppressed enzyme activity but also downregulated gene expression. Furthermore, inhibition of RpGS led to a marked decrease in the abundance of the obligate symbiont Buchnera and reduced the fecundity of R. padi. The transcript levels of RpVg and RpGT were also downregulated. These findings underscore the significant role of RpGS in regulating fecundity, suggesting its potential as a target for insecticide development in pest management strategies.